European Integration: Partisan Motives or Economic Benefits? - Patricia Esteve-González; Bernd Theilen (London School of Economics and Political Science (LSE), European Institute, 2014)
In this paper we examine the influence of economic factors on partisan support for European integration over the last three decades. We find that partisan support is larger in 'poorer' countries with direct economic benefits from EU membership. On the other hand, parties in countries affected by the Maastricht criteria are more Euro-sceptical. We also find weak evidence for larger partisan support in countries with more developed welfare states, and that the support for European integration fluctuates in parallel with the business cycle. Finally, our results indicate that the importance of economic factors in determining partisan support for European integration has grown in recent periods.
Keywords: F15; F42; F53; F55; H60; 330; European Integration; Partisan Ideology; Maastricht Criteria; European Budget; Benefits from Trade